2018
DOI: 10.2516/ogst/2018050
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evaluation of near wellbore stimulation – using electrical explosion shockwave on tight sand reservoir

Abstract: In recent years, the application of electrical explosion shockwave as a stimulation technology is increasing in oil fields, but lacks relevant theoretical knowledge to support it. In view of this problem, a research was carried out on experimental study of electrical explosion shockwave stimulation on the tight sand reservoir to determine the effective range of the resulting effects. An experimental platform for testing electrical explosion shockwave is established. Porosity, permeability and other mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 33 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…17 He et al carried out experiments to study the propagation of the explosion shock wave and the effective range of changes in permeability of the tight sand core samples caused by electrical explosion. 18 Maurel et al researched the facture characteristic of tight reservoirs and the permeability change under the effect of HVEP, and concluded that HVEP may replace the hydraulic fracturing in oil production. 19 The use of electrical pulses in enhancing the permeability of coal seam has attracted much attention.…”
Section: Introductionmentioning
confidence: 99%
“…17 He et al carried out experiments to study the propagation of the explosion shock wave and the effective range of changes in permeability of the tight sand core samples caused by electrical explosion. 18 Maurel et al researched the facture characteristic of tight reservoirs and the permeability change under the effect of HVEP, and concluded that HVEP may replace the hydraulic fracturing in oil production. 19 The use of electrical pulses in enhancing the permeability of coal seam has attracted much attention.…”
Section: Introductionmentioning
confidence: 99%